Real-time module for digital image processing developed on a FPGA - Mertes, Jacqueline G.; Marranghello, Norian [UNESP]; Pereira, Aledir S. [UNESP] (Elsevier, 2013)
Real-time processing emerged as an important component in the digital image processing area. The fast and convenient processing opens news possibilities, for example, configurable image processing modules in order to massive processing of images. With this purpose, this paper describes a colored digital image processing system. This system can configure a set of filters according to the prescriptions of a user, in order to adapt the system to the images to be treated. Six filters that perform the tasks of smoothing, edge detection, histogram equalization, color normalization and brightness normalization compose such a set. The system was described using System Verilog hardware description language, and implemented in an Altera FPGA. Due to its configurable characteristic, this system is capable of processing colored images for several applications such as agricultural and medical. © IFAC.
Keywords: Design systems; Digital circuits; Digital filters; Image processing; Real-time